Expanding the clinical and EEG spectrum of CNKSR2-related encephalopathy with status epilepticus during slow sleep (ESES). Issue 5 (May 2020) - Bonardi, Claudia M.; Mignot, Cyril; Serratosa, Jose M.; Giraldez, Beatriz G.; Moretti, Raffaella; Rudolf, Gabrielle; Reale, Chiara; Gellert, Pia M.; Johannesen, Katrine M.; Lesca, Gaetan; Tassinari, Carlo A.; Gardella, Elena; et al.
Highlights: Worsening of epilepsy associated with increment of awake spike-wave-index. A frontal topography of sleep EEG epileptic activity in the active phase of ESES. Language disorder due to speech/oro-motor dyspraxia. Abstract: Objective: To investigate the clinical and EEG features of Encephalopathy with Status Epilepticus during slow Sleep (ESES) related to CNKSR2 pathogenic variants. Methods: Detailed clinical history, repeated wakefulness/overnight sleep EEGs, brain MRI were collected in five patients, including one female, with CNKSR2 -related ESES. Results: Neurodevelopment in infancy was normal in two patients, delayed in three. Epilepsy onset (age range: 2–6 years) was associated with appearance or aggravation of cognitive impairment, language regression and/or behavioral disorders. Worsening of epilepsy and of cognitive/behavioral disturbances paralleled by enhancement of non-rapid eye movement (NREM) sleep-related, frontally predominant, EEG epileptic discharges [spike-wave-index (SWI): range 60–96%] was consistent with ESES. In three patients, episodes of absence status epilepticus or aggravation of atypical absences occurred, in this latter case associated with striking increment of awake SWI. Speech/oro-motor dyspraxia was diagnosed in four patients. In two patients, long-term follow-up showed epilepsy remission and persistence of mild/moderate cognitive disorders and behavioral disturbances into adulthood. Conclusions: Novel findings of our study are occurrence also in females, normal neurodevelopment before epilepsy onset, epilepsy aggravation associated with enhanced awake SWI, mild/moderate evolution in adulthood and language disorder due to speech/oro-motor dyspraxia. Significance: Our findings expand the phenotypic spectrum of CNKSR2 -related ESES.